Model and Validation of Single-Axis Tracking With Bifacial PV - Pelaez, Silvana Ayala; Deline, Chris; Greenberg, Peter; Stein, Joshua S.; Kostuk, Raymond K. (IEEE journal of photovoltaics, 2019)
Single-axis tracking is a cost-effective deployment strategy for large-scale ground-mount photovoltaic systems in regions with high direct-normal irradiance. Bifacial modules in 1-axis-tracking systems boost energy yield by 4%-15% depending on module type and ground albedo, with a global average of 9%. This benefit is in addition to the 15%-25% energy gain already afforded by single-axis tracking relative to fixed-tilt deployments. Here, we compare model results against field performance data for two side-by-side bifacial/monofacial tracked systems - one in Albuquerque, NM, USA, and one in eastern Oregon. The Albuquerque system shows monthly rear irradiance gain of 10%-14.9%, and the Oregon bifacial system has an average performance ratio 9.4% higher than the monofacial system. Both results match bifacial irradiance model results within uncertainty. Simulations show that smart tracking algorithms can offer more than 1% improvement on annual energy yield by adjusting tilt angle under cloudy conditions. Finally, ray-tracing simulations investigated edge brightening, suggesting a 15%-25% increase in rear irradiance at the ends of tracker rows, but up to 20% loss from center-mounted torque tubes, creating multiple shadows.